PENGARUH MEDIA SCRAPBOOK TERHADAP HASIL BELAJAR PKN KELAS I SD NEGERI 101884 LIMAU MANIS - Nurmasitah; Arrini Shabrina Anshor (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2021)
This study aims to determine whether there is an influence of scrapbook media on the learning outcomes of Civics Class 1 SD Negeri 101884 LimauManis. This research was conducted at SD Negeri 101884 LimauManis. The research sample was 30 students. The research method used in this research is quantitative research. The research design used in this study was a nonequivalent control group design. The instrument used was a multiple choice test to determine the effect of scrapbook media on Civics learning outcomes. From the data processing in the experimental class, the mean value of the pretest = 65.67, Standard Deviation = 6.51. and in the control class, the pretest value = 52.33, standard deviation = 5.63. The value of the average in the experimental class for the posttest = 93, Standard Deviation = 7.27. and the average value in the control class for the posttest = 59, Standard Deviation = 5.73. Then proceed with hypothesis testing using t test. After all the tests have been carried out, a higher average value can be obtained using scrapbook media and can be seen from the results of the calculation of tcount of 14.6, while the magnitude of ttable is 2.04. In other words tcount>ttable.it can be concluded that there is a significant effect of scrapbook media on the learning outcomes of Civics Class 1 SD Negeri 101884 LimauM